MEMRISTOR - INTRODUCTION INTO THE PROBLEMS - NEUMANN, Karel (Trends in education, 2009)
This contribution deals with the problems of memristor - a new component, which can probably change the world of information technologies. It gives basic information about memristor, its function and possible use.
Keywords: Memristor; hydro-mechanical analogy of memristor; memristor as a memory.